Types and degrees of vowel neutrality - Rebrus, Péter (Linguistica (Ljubljana), 2016)
This paper argues that neutrality in a harmony system is a gradient property since it is due to a vowel's participation in different patterns that are considered to be indicators of neutral behaviour in harmony. We examine three of these patterns of neutrality (transparency, affixal invariance and antiharmony) and show that a scale of neutrality can be defined on the basis of these patterns (their occurrence and variability) and the neutrality of harmony systems can be characterized with reference to this scale. We describe a tentative quantification of neutrality and then develop an explicit measure of neutrality based on relative word type frequency. This explicit measure is applied to the behaviour of neutral vowels in Hungarian front/back harmony where the different neutral vowels represent different degrees of neutrality in all three neutrality patterns.
Keywords: fonologija; harmonie vocalique; hongrois; Hungarian; madžarščina; phonologie; samoglasnik; samoglasniška harmonija; voyelle